Improving Basic Writing Competencies (Production Écrite Debutante) French Language Through the Application of Fiche De Travail Numérique - Isda Pramuniati; Abdul Ghofur; Wahyuni Sa’adah (Journal of Education Reseach and Evaluation, 2024)
In language learning, students must have language skills such as oral comprehension, written comprehension, oral production, and written production. However, there are still many students who have low writing skills. This research aims to analyze the application of digital worksheets to improve student's writing skills and assess the feasibility of digital worksheets in the Production Écrite Débutante course. This type of research is development. The procedure used to develop media is ADDIE (Analysis, Design, Development, Implementation, Evaluation). The methods used to collect data are observation, interviews, questionnaires and tests. The subjects of this research are material experts and learning media experts. Data collection instruments use questionnaires and test questions. The data analysis technique uses qualitative and quantitative descriptive analysis. The results of the research, namely the application of worksheets to students, showed significant changes in writing skills. The vocabulary indicator increased from 64.53 to 87.52. The grammar indicator increased from 56.83 to 87.33. The writing mechanism indicator increased from 81.69 to 92.35. The implementation results show that the average student learning outcome is 86.89. It was concluded that this digital worksheet can improve students' basic writing competencies. This research implies that the digital worksheets developed are suitable for use in learning.